Determinants of Long-Acting Reversible Contraceptive Method Utilization among Married Women in Assosa Town in Western Ethiopia: A Case-Control Study - Asefa Eticha; Gurmesa Tura; Tsedach Alemu (Mashhad University of Medical Sciences, 2019)
Background & aim: The prevalence rate of contraceptive use in Ethiopia is 42%; however, only 5% of Ethiopians use the long-acting contraceptive methods. This rate is 4.8% in Benishangul Gumuz Region in this country. Regarding this, the present study aimed to assess the determinants of long-acting reversible contraceptive method use among married women in Assosa town, Ethiopia. Methods: This community-based unmatched case-control study was conducted on 384 married women from April 26 to May 10, 2016. The study population consisted of the users (case group; n=128) and none-users (control group; n=256) of one of the long-acting methods. Multivariate logistic regression analysis was performed to identify the variables having a significant association. Results: A total of 382 women participated in this study with a response rate of 99.5%. The determinants of long-acting contraceptive use were identified as the lack of decision-making power (OR=0.29, 95% CI: 0.11-0.80), poor attitude toward such birth control methods (OR=0.13, 95% CI: 0.06-0.29), wrong expectation regarding method availability (OR=0.23, 95% CI: 0.07-0.73), low level of knowledge about long-acting contraceptive methods (OR=0.19, 95% CI: 0.08-0.47), future intention to get pregnant (OR=0.39, 95% CI: 0.18-0.82), and walking distance of more than 30 min from associated health facilities (OR=0.36, 95% CI: 0.15-0.85). Conclusion: Women's decision-making power, knowledge and attitude regarding contraceptives, expectation regarding method availability, distance from associated facilities, and intention to get pregnant in the future were identified as the independent predictors of long-acting contraceptive method use.